2016
DOI: 10.3946/kjme.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perceptions and satisfaction level of hybrid problem-based learning for 16 years in Kyungpook National University School of Medicine, Korea

Abstract: Purpose:Kyungpook National University School of Medicine has been implementing hybrid problem-based learning (PBL) since 1999. The aim of this study was to investigate the changes in the students’ perceptions and satisfaction levels of hybrid PBL.Methods:The target period of our study was from 1999 to 2014, and target subjects were second-year medical students in Kyungpook National University School of Medicine. The survey was conducted at the end of semester. We had a focused interview with group leaders and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
2
4
0
5
Order By: Relevance
“…The aims of medical curriculum are not limited to gather knowledge but also to develop student’s non-cognitive factors crucial for the future needs of the profession. The present study confirmed that MAHSA University medical students appreciated PBL as a learning tool that is in accordance with findings from other studies done in different medical schools [6,18,19]. The present study also showed a high sense of ASC and a moderate level of ILOC which could be attributed to their appreciation of PBL as evidenced by the statistically significant positive correlation between students’ attitude towards PBL with ASC and LOC reported in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…The aims of medical curriculum are not limited to gather knowledge but also to develop student’s non-cognitive factors crucial for the future needs of the profession. The present study confirmed that MAHSA University medical students appreciated PBL as a learning tool that is in accordance with findings from other studies done in different medical schools [6,18,19]. The present study also showed a high sense of ASC and a moderate level of ILOC which could be attributed to their appreciation of PBL as evidenced by the statistically significant positive correlation between students’ attitude towards PBL with ASC and LOC reported in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…This enables students to retain information which can be greater applied for use in future practice, rather than primarily learning for examination purposes. Moreover, this teaching style concurs with Yeo and Chang’s study regarding the impact of PBL on student satisfaction, where synchronicity with ongoing lectures can improve curricula perception [ 5 ].…”
Section: Main Textsupporting
confidence: 85%
“…16 The emerging themes in student reflections are similar to other published studies. 17,18 Team based learning, collaboration, innovative learning method, quest for knowledge, long term retention have been reported earlier. Social accountability is a novel soft skill that emerged in student reflections.…”
Section: Discussionmentioning
confidence: 91%